Molecular mapping of stem rust resistance genes in wheat - Wu, Shuangye (Kansas State University, 2008)
Stem rust, caused by Puccinia graminis f. sp. tritici, has successfully prevented rust epidemics by Deployment of resistant cultivars in the past several decades. Unfortunately, race TTKS (termed Ug99) has defeated most stem rust resistance genes existing in commercial cultivars. Sr40, a stem rust resistance gene from Triticum timopheevii ssp. araraticum, was transferred to wheat and provides effective levels of seedling and adult plant resistance against Ug99. To characterize Sr40 in wheat, two mapping populations were developed from the crosses RL6088 / Lakin and RL6088 / 2174. RL6088 is an Ug99-resistant parent with Sr40. Since race TTKS is a quarantined pathogen, a US stem rust isolate RKQQ that is avirulent to Sr40 was used to evaluate the rust resistance in the F[subscript]2 and F[subscript]2:3 populations at the seedling stage. A total of 83 simple sequence repeats (SSR) primers on chromosome 2B were used to screen the parents for polymorphism. Each F[subscript]2 population was analyzed with the markers polymorphic between two parents. Marker Xwmc344 was the most closely linked to Sr40, at 0.7 cM proximal, in the linkage map constructed from the population RL6088 / Lakin, while Xwmc474 and Xgwm374 were also tightly linked. Xwmc474 was mapped 2.5 cM proximal to Sr40 in the RL6088 / 2174 population. Xwmc474 and Xwmc661 were flanking markers for Sr40 in both populations. Markers linked to Sr40 will be useful for marker-assisted integration of Sr40 into elite wheat breeding lines. In addition, a unknown stem rust resistance gene from another source, OK01307, a breeding line from Oklahoma State University shows partial resistance to Ug99, and was characterized using SSRs in this study. Two mapping populations were developed from cross OK01307 / Chinese Spring and OK01307 / LMPG-6. A total of 1300 SSR primers were screened for polymorphism between OK01307 and Chinese spring, and 1000 SSR primers were screened for polymorphism between OK01307 and LMPG-6. Polymorphic primers between parents and between bulks were used to screen the corresponding population. One Sr gene in OK01307 was mapped on chromosome 1BS of the both populations, which was closely linked to Sr24. Whether the gene is Sr24 per se or a new Sr gene that closely linked to Sr24 needs further investigation.
Keywords: Molecular mapping; Stem rust; Wheat; Agriculture, Agronomy (0285)